Unraveling the mechanism of the oxidation of glycerol to dicarboxylic acids over a sonochemically synthesized copper oxide catalyst. Issue 12 (24th May 2018) - Amaniampong, Prince N.; Trinh, Quang Thang; Varghese, Jithin John; Behling, Ronan; Valange, Sabine; Mushrif, Samir H.; Jérôme, Francois
Abstract : Glycerol was oxidized selectively to oxalic and tartronic acids in 78% yield over a highly crystalline CuO catalyst prepared within a few minutes by a sonochemical synthesis. Abstract : The utilization of low frequency ultrasound (US) offers a straightforward and powerful tool for the production of nanostructured materials, in particular for structurally stable, highly crystalline, and shape-controlled catalytic materials. Herein, we report an unconventional strategy for the synthesis of CuO nanoleaves within 5 min of US irradiation. The as-obtained CuO nanoleaves were found to be selective in the base-free aqueous oxidation of glycerol to dicarboxylic acids (78% yield of tartronic and oxalic acids), in the presence of hydrogen peroxide (H2 O2 ) and under mild reaction conditions. Density Functional Theory (DFT) investigations revealed a synergy between the CuO catalyst and H2 O2 in maintaining the structural integrity of the catalyst during the reaction, creating alternative efficient pathways for the selective formation of dicarboxylic acids. Isotope labeling experiments using H2 18 O2 further confirmed that oxygen from hydrogen peroxide, not from CuO, was preferentially incorporated into the dicarboxylic acid, significantly preserving the monoclinic structure of the CuO catalyst.